[68Ga-]PSMA-11 PET/CT and multiparametric MRI for gross tumor volume delineation in a slice by slice analysis with whole mount histopathology as a reference standard – Implications for focal radiotherapy planning in primary prostate cancer. (December 2019) - Bettermann, Alisa S.; Zamboglou, Constantinos; Kiefer, Selina; Jilg, Cordula A.; Spohn, Simon; Kranz-Rudolph, Jasmin; Fassbender, Thomas F.; Bronsert, Peter; Nicolay, Nils H.; Gratzke, Christian; Bock, Michael; Ruf, Juri; et al.
Highlights: PSMA-PET has an excellent accuracy and the sensitivity is superior to mpMRI in intraprostatic GTV delineation. Delineations based on mpMRI significantly underestimate real tumor volume validated by histopathology. PSMA-PET may be an alternative focal treatment planning tool for more precise and personalized treatment. Abstract: Background and purpose: Focal therapies are a promising approach to treat prostate cancer (PCa) more precisely instead of conventional whole gland treatment. Nowadays, multiparametric MRI (mpMRI) is routinely used for gross tumor volume (GTV) delineation. The aim of our study was to compare PSMA-PET/CT and mpMRI for the delineation of intraprostatic tumor burden by using whole mount histopathology as a reference standard. Material and methods: 17 prospectively enrolled patients with primary PCa underwent [ 68 Ga-]PSMA-11 PET/CT and mpMRI before radical prostatectomy. PSMA-PET/CT, mpMRI and histopathology of the resected specimens were co-registered. Two teams of experts generated GTV contours for mpMRI and PET, respectively. The imaging was validated on a lesion level and slice by slice in quadrants based on the distribution of PCa in histopathology. Overall, 772 quadrants were analyzed with 414 being true positive for tumor (53.6%). Results: Median tumor volumes were 10.4 ml for GTV-histo, 10.8 ml for PSMA-PET and 4.5 ml for mpMRI. Median tumor volume in mpMRI was significant ( p < 0.05) smaller than GTV-PET and GTV-histo, respectively. The sensitivity and specificity were 86% and 87% for PSMA-PET, 58% and 94% for mpMRI and 91% and 84% for their GTV-union. In 133 quadrants PSMA-PET/CT correctly identified tumor where mpMRI found none. MpMRI identified 19 true positive quadrants exclusively. Conclusion: Our investigation demonstrates an increased consensus of PSMA-PET with histopathology compared to mpMRI for intraprostatic GTV delineation, especially with a higher sensitivity. Additionally mpMRI contours underestimate tumor volume significantly. Thus PSMA-PET may be a complementary augmentation for GTV delineation in focal therapies.